ANALISIS RISIKO KESEHATAN LINGKUNGAN PAPARAN HIDROGEN SULFIDA (H2S) DAN AMONIA (NH3) PADA MASYARAKAT DI TPA PIYUNGAN - Farisa Hidayatullah; Surahma Asti Mulasari; Lina Handayani (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2021)
Piyungan landfill is a waste final processing site that is still active now. Waste in the Piyungan landfill produces hydrogen sulfide (H2S) and ammonia (NH3) gases. The gas comes from the anaerobic decomposition of waste by microorganisms. The purpose of this study is to analyze the health risks of hydrogen sulfide and ammonia exposure in the community at Piyungan landfill. This study was descriptive research and used quantitative analysis. The research design was cross-sectional with the environmental health risk analysis approach. The research sample is the people of Ngablak hamlet, which live in a zone of ± 600 meters from the Piyungan landfill. The sampling technique used purposive sampling, and the sample size was 59 people. The results showed that the risk level (RQ) of hydrogen sulfide was 1.2163 (RQ > 1), while the ammonia level was 0.0203 (RQ ≤ 1). Based on these results, the level of risk due to exposure to hydrogen sulfide is said to be unsafe. However, exposure to ammonia is said to be safe or not at risk of causing health problems in the community. The research is expected to be useful for improving the waste management system at TPA Piyungan and public awareness of processing waste.